New directions in stochastic multicriteria acceptability analysis - Tervonen, Tommi (Turun yliopiston julkaisuja, ISSN 0082-7002, 2007)
Extended abstract in Finnish. - Extended abstract in Portuguese.
Keywords: päätöksenteko; tietotekniikka; matematiikka